Transparent organic photodiodes for high-detectivity CMOS image sensors - Park, Sungjun; Lim, Younhee; Heo, Chul Joon; Yun, Sungyoung; Leem, Dong Seok; Kim, Sunghan; Choi, Byoungki; Park, Kyung Bae (Optica, 2022)
The demand for high-definition complementary metal-oxide-semiconductor (CMOS) image sensors has increased considerably over the past few years in industry as well as in academia. Here we propose transparent green-sensitive organic photodetectors (TG-OPDs) with both dark-current-based high detectivity (over 1014 cm Hz1=2 W-1 at a wavelength of 550 nm under 3 V) and high responsivity (0.34 AW-1 under 3 V) for organic-silicon hybrid CMOS image sensors. A bathocuproine V C60 electron-transporting layer provided the fabricated TG-OPDs with a minimal junction resistivity, smooth morphology, and desirable energy level modulation, resulting in exceptional light sensitivity, a low dark current (below 10-11 A cm-2), and a high rectification ratio spanning 10 orders of magnitude. The TG-OPDs had high-temperature endurance (up to 150°C for 2 h) and operational stability under intense heat (above 85°C) for 50 d. We expect this performance to enable the industrialization of these TG-OPDs for optoelectronic sensor applications, such as photoplethysmography, fingerprint recognition, proximity sensing, and imaging.
Keywords: Bathocuproine; Complementary metal oxide semiconductors; Detectivity; Electron transporting layer; High definition; Orders of magnitude; Organic photodiodes; Organics; Rectification ratio; Responsivity